Relationship Between Self-Management and Perceived Performance Among Chinese Combat Sports Athletes - Changxu Zhang; 박순문 (International Journal of Advanced Culture Technology(IJACT), 2025)
We investigate how participation barriers in Taekwondo affect the consumption desire and participation intention of Chinese youth. To achieve this objective, the study targeted Chinese adolescent Taekwondo practitioners. A total of 400 survey responses were collected through convenience sampling via an online platform. After excluding 50 invalid responses due to insincerity or duplication, data from 350 respondents (200 males and 150 females) were included in the final analysis. The research employed a questionnaire survey method, using scales that had been validated for reliability and validity in previous studies. These were revised and supplemented appropriately for the current study. The questionnaire items were rated on a 5-point Likert scale. The collected data were analyzed using SPSS 22.0, applying statistical methods aligned with the research objectives. The findings are as follows: First, Taekwondo participation barriers were found to partially influence consumption desire. Second, Taekwondo participation barriers were also found to partially affect participation intention. Third, Taekwondo consumption desires were partially influential on participation intention.